The Implementation of Total Quality Management (TQM) to Improve Learning Quality in Schools - Faza Andary; Wahab; Sugeng Listyo Prabowo (Universitas Nurul Jadid, 2025)
This study aims to describe and analyse the implementation of Total Quality Management (TQM) in improving learning quality. Using a qualitative, descriptive case study design, the research explored how TQM principles were integrated into school management and instructional practices. Data were collected through interviews, observations, and documentation involving the principal, six teachers, one administrative staff member, and two parents. The findings reveal that TQM is implemented through participatory Leadership, teacher empowerment, effective management of learning facilities, and continuous evaluation based on the Plan–Do–Check–Act (PDCA) cycle. Leadership plays a crucial role in coordinating teacher collaboration and sustaining school improvement. Teacher empowerment is fostered through training, mentoring, and reflective discussions. The management of learning facilities and infrastructure demonstrates adaptive use of limited resources supported by community involvement. Evaluation is conducted systematically to ensure continuous feedback and improvement. The study concludes that implementing TQM has created a culture of collaboration, accountability, and innovation. The research implies that TQM principles can be effectively adapted in resource-limited schools through participatory management, reflective evaluation, and community partnerships to strengthen sustainable quality assurance in education.